Kirkemosegård – Et offerfund med smykker fra ældre germansk jernalder - Clemmensen, Benita (Kuml, 2014)
Kirkemosegård – a votive site with ornaments from the Early Germanic Iron Age The Kirkemosegård ornaments were recovered following a metal detector survey and subsequent archaeological investigations of the find site in a cultivated field with wet hollows at Spentrup, north of Randers (fig. 2). The archaeological investigations showed that the finds probably represent a votive deposit on the margin of a wetland area referred to on historical maps as Kirkemose (figs. 3‑4). The offering comprises a button-bow fibula, six scutiform and four circular pendants, all of gold (fig. 1). All the objects had been ploughed up and lay in the plough soil. The precise location where the gold objects had originally been buried could not be identified during the excavation, but careful recording of their distribution in the plough soil makes it possible to narrow down the area of their deposition. There is a concentration of finds roughly in the middle of the excavation trench, around which the other objects are distributed. It must be within this area that the ornaments were originally deposited (fig. 3). This article includes a detailed description of the individual ornaments. In general terms, the fibula can be described as a hollow construction of sheet gold with a stabilising clay core (fig. 10). The upper surface is decorated with filigree consisting of very small rings of miniature beaded wire soldered on to and covering the entire surface (figs. 5 and 11). Along the edges, slightly heavier beaded wire has been used as a frame. The fibula measures c. 8 cm in length. Gemstones and glass were mounted in cloisonné, in which the cells were formed of smooth gold bands. Some of the settings contain red stones, probably garnets, while others hold a yellowish-green fragmented mass, presumably degraded glass (figs. 6, 8, 9, 12). On the foot of the fibula there is a stylised fish-like bird and two stylised bird’s heads with curved beaks (fig. 13). The catch consisted of a silver pin construction (fig. 7). The four circular gold pendants have diameters of 1.19‑1.32 cm and a weight of c. 1.2‑2.1 g (fig. 14). They are constructed in openwork with three rings of smooth or beaded filigree wire forming an edge. The suspension loops consist of ribbed gold band. Three of the pendants have the same pretzel-shaped motif at their centre – a kind of scutiform figure. Two of the pendants have two of these figures and the third has three. Soldering traces indicate that there were also originally motifs at the centre of the fourth pendant. The six scutiform pendants can be divided up into two types, based on their size, method of manufacture and decoration. They do, however, possess common features. They all have a band-like ribbed suspension loop and are edged with beaded filigree wire. Moreover, at their sides, at the transition to the side-pieces, there are rings of filigree wire with bosses, two punched concentric circles or granulation spheres at their centre. This is interpreted as depicting the eye of an animal seen in profile. They probably represent bird’s heads, where the side-pieces represent a curved beak. The round eye and the hooked beak are typical of the early animal style of the Early Germanic Iron Age. They constitute mirror images about a vertical axis and there is thereby symmetry in their decoration. The three small crescent-shaped pendants measure 1.21‑1.23 cm at their broadest point and have a height of 1.18‑1.23 cm from the top of the suspension loop to the base. They weigh 0.65‑0.74 g. They were stamped using the same die and are decorated with filigree (figs. 15‑16). The three large crescent-shaped pendants have a width of 1.59‑1.65 cm at their broadest point, a height of c. 1.5 cm and a weight of 1.12‑1.82 g (fig. 17). They are individually decorated from the front with stamped circular patterns consisting of two concentric circles, pretzel-shapes – small representations of the form of these ornaments – and figures of eight in filigree as well as granulation in the form of individual gold beads. The pendants show obvious traces of use wear, evident in that the outer surface of the beaded wire has been worn smooth along the edge. The beaded relief is more distinct inside the suspension loops (fig. 18). Greater wear is also evident on each side of these loops than further down the sides. This wear was possibly caused by spacers in the form of beads or knots intended to hold the pendants apart (fig. 18). Several of the pendants have visible wear to the suspension loops, interpreted as being due to suspension on a string, plaited leather thong or chain. The Kirkemosegård ornaments were not found in a datable context and their age and origin has therefore been ascertained on the basis of a description and discussion of parallel finds. There are not many gold filigree fibulas of Kirkemosegård type, but examples are known from Skodborg in southern Jutland, Elsehoved in southeast Funen and Kitnæs near Roskilde Fjord. There are also fragments from Rytterbakken on Bornholm (fig. 19), Adslev near Aarhus and Nørre Tranders in Aalborg. On the basis of these parallels, the Kirkemosegård fibula is dated to the early 6th century AD. Filigree fibulas are only known from southern Scandinavia. There are several known examples of circular pendants resembling those from Kirkemosegård. This ornament type can take various forms, but basically consists of a garland of smooth or beaded ring with a beaded wire running around the inside and outside. In most cases there are three rings, but examples exist with two or four rings. The centre of the pendant can be open or decorated with two or three pretzel-shaped motifs, various forms of crosses and spiral motifs (figs. 20‑22). Apart from Denmark, this ornament type is also known from England, Norway, Sweden and southwest Germany. The circular pendants from Denmark are generally dated to the Early Germanic Iron Age. Scutiform pendants are considered to be of Roman origin and are known from the late 2nd century AD. Their occurrence extends over a longer period of time and in many respects they represent a very heterogeneous group of finds that, in addition to pendants, also includes hanging ornamental plates on hair pins, jingle-plates on horse harness and tack and belt ornaments. The scutiform pendants show contacts towards the southeast to the Black Sea area – links that extend at least as far back as for example the Brangstrup hoard found in southeast Funen that includes examples thought to have been manufactured in the 4th century AD in the Black Sea area. Scutiform pendants have a wide geographic distribution and long period of use, as there are also records from the 7th century in England. The execution of the ornaments, and motifs employed, show that they were probably manufactured in southern Scandinavia. Comparisons with the various parallel finds indicate that the Kirkemosegård ornaments should be dated to the early 6th century AD. These are ornaments that clearly are worn, showing that they were either heavily used by their owner or of considerable age when offered. On their own, these finds give only a very fragmentary picture of the local cultural landscape in the Iron Age. Settlement traces and graves (fig. 23) that have been investigated demonstrate that the area was populated at this time, but they provide no indication of the immediate presence of the social elite of which the Kirkemosegård hoard is a clear expression (fig. 24). Benita Clemmensen Museum Østjylland